Analysis of the Calculation of Rigid Pavement Thickness on Jalan Guyangan - Simpang Empat Candi - Supriadi Supriadi; Edy Gardjito; Sigit Winarto; Fajar Romadhon (Litbang Pemas - Universitas Islam Lamongan, 2021)
There are several factors that need to be considered in road development planning, such as soil structure, traffic conditions, rainfall, and drainage networks. These things need to be considered because they affect the quality of the road. The road guyangan – simpang empat candi is the main road with a flexible pavement structure. The structure is deemed not suitable for a load of passing vehicles. In terms of these conditions, it is necessary to change the pavement structure to the rigid pavement. The rigid pavement itself is an arrangement of road pavement structures which on the top layer uses cement concrete plates. This study aims to plan the thickness of the rigid pavement, the characteristics of the concrete, and the required budget. The method used to plan is by using the 2017 revised road pavement design manual method. The calculation results obtained concrete with quality class III with 28 days of compressive strength of 350 kg / cm2, the thickness of concrete slab 305 mm with details of the cost of Rp. 12,746,095,600.00 (Twelve billion seven hundred forty-six million ninety-five thousand six hundred rupiahs).